The resumption of sports competitions after COVID-19 lockdown: The case of the Spanish football league - Buldú, J. M.; Antequera, D. R.; Aguirre, J. (Chaos, Solitons & Fractals, 2020)
In this work, we present a stochastic discrete-time SEIR Susceptible-Exposed-Infectious-Recovered model adapted to describe the propagation of COVID-19 during a football tournament. Specifically, we are con- cerned about the re-start of the Spanish national football league, La Liga , which is currently -May 2020-stopped with 11 fixtures remaining. Our model includes two additional states of an individual, confined and quarantined, which are reached when an individual presents COVID-19 symptoms or has undergone a virus test with a positive result. The model also accounts for the interaction dynamics of players, consid- ering three different sources of infection: the player social circle, the contact with his/her team colleagues during training sessions, and the interaction with rivals during a match. Our results highlight the influence of the days between matches, the frequency of virus tests and their sensitivity on the number of players infected at the end of the season. Following our findings, we finally propose a variety of strategies to minimise the probability that COVID-19 propagates in case the season of La Liga was re-started after the current lockdown.